(untitled) (ESMAT Magazine, 2024)
Legal responsiveness, highlighted as the theme of this work, is delimited within the field of the Theory of Responsive Regulation and consists of a model of regulation and application of law whose purpose is to be effective and adaptable to the variable needs of societies. On the other hand, the asynchrony between law and reality has become more pronounced as the progress of new technologies, integrated into social life, has occurred at an unmeasured and unexpected speed, unlike any previous era, with emphasis on the evolution of artificial intelligence systems. In view of this prognosis, it becomes relevant to consider a regulatory formula/model that proves more adequate to the rapid and disruptive technological march. In this sense, the research problem is posed from the following perspective: How to mitigate the asynchrony between law and the swift technological evolution? The objectives of the research are, in general, to evaluate the efficiency of the responsive regulatory system and, specifically, to analyze the elements of the theory of responsive regulation and finally to investigate whether Bill 2338/2023 (Legal Framework of Artificial Intelligence) presents a responsive approach in its regulatory model. The hypothesis is predisposed to recognize responsive regulatory modeling as a legal technique capable of better facing the regulatory challenges of artificial intelligence in Brazil. The research adopted the hypothetical-deductive method, and its approach is based on theory and legislation, that is, the use of books, scientific articles, and laws.